Effect of operating conditions on batch and continuous paracetamol crystallization in an oscillatory flow mesoreactor. Issue 47 (18th November 2016) - Cruz, P.; Rocha, F.; Ferreira, A.
Abstract : The batch and continuous crystallization of paracetamol from aqueous solutions is studied in a novel oscillatory flow mesoreactor. Abstract : The batch and continuous crystallization of paracetamol from aqueous solutions is studied in a novel oscillatory flow mesoreactor equipped with smooth periodic constrictions. The aim of this study is to evaluate the influence of the operating and thermodynamic variables on the size of the crystals for enhanced direct crystallization of micronized powders. It was found that mixing intensity, supersaturation and temperature determine the crystal size properties. Evaluating the results according to the classical nucleation theory, it was observed that the kinetic and the thermodynamic parameters are mainly influenced by the mixing intensity and by the crystallization temperature, respectively. The continuous-flow operation mode was revealed to be more suitable in the production of inhalable size particles because it provides smaller residence times and reduced friction, breakage and aggregation phenomena. Growth kinetic data were also obtained. This new reactor showed great potential to be used for direct crystallization of this drug for pulmonary drug delivery.